2022
DOI: 10.1186/s40359-022-01013-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Chinese version of the COVID-19 Phobia Scale

Abstract: Background The COVID-19 pandemic has become a source of fear worldwide and has negative mental health effects on the general population. In 2022, the epidemic continues to be characterized by many points, widespread and frequent in China, and the situation is serious and complex. To provide an effective and scientific tool, the study validated the Chinese version of the COVID-19 Phobia Scale (C19P-SC). Methods This study selected 1138 Chinese indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…The median of PTSS was 24 (IQR, [19][20][21][22][23][24][25][26][27][28][29][30][31][32], ranging from 17 to 85. According to the critical value of PCL-C in the screening for PTSS [30], 230 medical students had PTSS among 2208 medical students.…”
Section: Status Of Post-traumatic Stress Symptomsmentioning
confidence: 99%
“…The median of PTSS was 24 (IQR, [19][20][21][22][23][24][25][26][27][28][29][30][31][32], ranging from 17 to 85. According to the critical value of PCL-C in the screening for PTSS [30], 230 medical students had PTSS among 2208 medical students.…”
Section: Status Of Post-traumatic Stress Symptomsmentioning
confidence: 99%
“…The Chinese version of the Simplified Coping Style Questionnaire (SCSQ) was also used for evaluation. Xie ( 1998 ) used the SCSQ, which was prepared on the basis of domestic and foreign theories on coping styles. There were 20 items and two dimensions in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Students indicated the frequency of their perceived peer victimization using a six-point Likert scale (1 = never ; 6 = every day ). Prior studies have shown that the DBVS-S Chinese Version has high internal consistency (α = 0.70 to 0.82) and strong evidence of validity (Xie et al, 2016). The physical, verbal, and relational victimization subscales also have high internal consistency (α = 0.76 to 0.90; Wang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Students responded to items on a 4-point Likert scale (1 = strongly disagree ; 4 = strongly agree ). The Chinese version has shown high reliability (0.80) and strong evidence of validity (Xie et al, 2016). Like peer victimization, the internal consistency was high (α = 0.73 to 0.84; Wang et al, 2018).…”
Section: Methodsmentioning
confidence: 99%